Digitalization, Financial Development, Trade, and Carbon Emissions; Implication of Pollution Haven Hypothesis During Globalization Mode - Ke, Jiaming; Jahanger, Atif; Yang, Bo; Usman, Muhammad; Ren, Fei (Frontiers in Environmental Science, 2022)
In the modern era of globalization, information and telecommunication technologies (ICTs) have become an important factor influencing carbon dioxide (CO2) emission; however, the specific effect produced by ICTs is still not clear. Therefore, the study examines the nexus between ICTs, foreign direct investment, globalization, and CO2 emission in 77 developing countries. The novel attribute of this research is that the ICTs with financial development and the international trade interaction term. The results of this study are based on pooled regression and generalized method of moments (GMM) techniques from 1990-2016. The subsequent empirical findings are established as follows: first, the ICTs positively contribute to reducing CO2 emission. Second, globalization significantly increases the CO2 emission; third; the interaction between ICTs and financial development increases CO2 emissions, and the moderating effect of ICTs and international trade do the similar. Fourth, the empirical finding verifies the presence of the pollution haven hypothesis. Fifth, our robustness tests are conformed that our empirical results were consistent. We suggest that policymakers should be using ICTs as a policy tool to mitigate CO2 emission and should invite such investments in ICTs sectors, which help to maintain the environment quality.